MULTIDRUG-RESISTANT ACINETOBACTER BAUMANNII PREVALENCE AND CHARACTERISTICS IN DR.WAHIDIN SUDIROHUSODO GENERAL HOSPITAL OF MAKASSAR - Dewi Tungadi; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
BackgroundMultidrug-resistant Acinetobacter baumannii (MDRAB) is a strain of Acinetobacter baumannii which is resistant to three or more classes of antibiotics. As prevalence of MDRAB increases, the antibiotics of choice become limited. Identification of MDRAB is required to manage and control infection.MethodThis was a retrospective study, conducted in Dr. Wahidin Sudirohusodo General Hospital of Makassar, dated from January to December 2016. Bacterial identification and antimicrobial susceptibility testing (AST) were performed using VITEK 2. The patient data were obtained from electronic medical records.Results and DiscussionA total of 323 Acinetobacter baumannii isolates were obtained, consisted of 188 isolates in January-June 2016 and 36 of which was MDRAB (19.15%) with the average length-of-stay 33 days; and 135 isolates in July-December 2016 and 31 of which was MDRAB (22.96%) with the average length-of-stay 27 days. MDRAB was mostly discovered from patients using 3 or more medical devices and on single antibiotic therapy. MDRAB isolates were mostly obtained in sputum and pus specimens, and majority of patients had respiratory diseases. The result of AST showed 100% and 96% susceptibility to Polymyxin B; 71.43% and 54.84% susceptibility to Amikacin; 66.67% and 50% susceptibility to Trimethoprim/Sulfamethoxazole in January-June and July-December 2016, respectively.Conclusion and SuggestionsThe prevalence of MDRAB in our hospital in 2016 was high, suggesting the needs to improve hospital infection prevention and control. Polymyxin B, Amikacin, and Trimethoprim/Sulfamethoxazole are the antibiotics of choice to treat MDRAB.